Reduced thermal performance of kelp recruits under an upwelling-limited climate change scenario - Bianca Reis; João N. Franco; Cheyenne Oliveira; Katerina Economou; Maria F. Sá; Isabel Sousa-Pinto; Francisco Arenas (Algal Research, 2026)

Corrigendum to “ENSO-driven distribution shifts in the critically endangered Mustelus whitneyi along the Northern Peruvian Coast” [Mar. Environ. Res. (220) 1-10 108187] - Juliana López-García; Andrés F. Navia; Víctor Hugo Cruz-Escalona; Joanna Alfaro-Shigueto; Jeffrey C. Mangel; Francisco Javier Urcádiz-Cázares; Carlos Yáñez-Arenas (Marine Environmental Research, 2026)

ENSO-driven distribution shifts in the critically endangered Mustelus whitneyi along the Northern Peruvian Coast - Juliana López-García; Andrés F. Navia; Víctor Hugo Cruz-Escalona; Joanna Alfaro-Shigueto; Jeffrey C. Mangel; Francisco Javier Urcádiz-Cázares; Carlos Yáñez-Arenas (Marine Environmental Research, 2026)

Macrofaunal diversity and secondary production in kelp holdfasts (Phaeophyceae) within a climatic transition zone - Bianca Reis; João N. Franco; Dimítri A. Costa; Harold Casalís-Cantallo; Pieter van der Linden; Isabel Sousa-Pinto; Francisco Arenas; Carlos Antunes; Iván F. Rodil (Marine Environmental Research, 2026)

What drives cultural ecosystem services in mountain protected areas? An AI-assisted answer using social media data - José Carlos Pérez-Girón; Carlos Javier Navarro; Akram Elghouat; Rohaifa Khaldi; Domingo López-Pacheco; Salvador Arenas-Castro; Ana del Águila; Ricardo Moreno-Llorca; Nuria Pistón; Luis F. Romero; Ana Sofía Vaz; Siham Tabik; et al. (Ecosystem Services, 2026)

Population genetics and lineage structure of the endangered Bolivian chinchilla rat Abrocoma boliviensis - Daniela Arenas-Viveros; Teresa Tarifa; Marisol Hidalgo-Cossio; Omar F. Osco; Ximena Velez-Liendo; Jorge Salazar-Bravo (Conservation Genetics, 2026)
Studies on conservation genetics of endangered species can identify which populations should be the focus of management plans. The endangered Bolivian chinchilla rat, Abrocoma boliviensis , is currently threatened by its rarity and anthropogenically driven transformation of the landscape it inhabits. Given its conservation status, restricted geographic range and limited information about its natural history, understanding how its genetic diversity is apportioned is crucial to inform any potential conservation efforts for A. boliviensis . In this study, we assessed the genetic diversity and population structure of A. boliviensis as a first approximation to a comprehensive evaluation of the species. Mitochondrial data from 12 individuals revealed high levels of genetic distance, nucleotide diversity and polymorphisms, all of which indicate the existence of three separate clades. This was further supported by reduced-representation genomic data, which showed little to no admixture between these clades. This lack of gene flow suggests that the lineages have followed separate evolutionary trajectories and should be recognized, at minimum, as distinct evolutionarily significant units. Our contribution highlights the urgency with which survey efforts must become the first order of action. The generation of new population-level data will be essential to refine our understanding of the species, clarify the evolutionary trajectories of its lineages, and inform effective conservation strategies.

Grid extension vs. off-grid systems in rural Areas: Methodologies, tools, and criteria for decision-making - César Y. Acevedo-Arenas; Julian E. Guerrero-Macias; Yecid A. Muñoz-Maldonado; Johan S. Amado-Alvarado; Johann F. Petit-Suárez (Utilities Policy, 2026)

Rising herbivory pressure of Sarpa salpa and the emerging threat to Southern European marine forests - J. de Azevedo; J.N. Franco; M. Dolbeth; H.S. Meyer; A. Barreiro; E.A. Salas-Leitón; F. Arenas (Marine Environmental Research, 2026)

Middle Bronze Age axes from the eastern Adriatic: towards the reconstruction of copper supply networks in the 2nd millennium BC - Mario Gavranović; A. Arena; M. Mehofer; N. Mittermair; F. Franković; D. Kliškić; D. Domazet; N. Čondić (Archaeological and Anthropological Sciences, 2026)
This study presents chemical (ED-XRF) and lead isotope (HR-MC-ICP-MS) analyses of 29 bronze axes recovered along the eastern Adriatic coast, offering new insights into the metallurgical background of archaeological types with distinct distribution patterns. The analysed axes date from the Middle to the early Late Bronze Age (17th − 14th centuries BC), a crucial period marked by intensified copper production in emerging Alpine mining districts and the decline of other metallurgical centres, such as those in eastern Serbia. Due to scarcity of analytical data and lack of closed contexts, the role of the eastern Adriatic within the dynamic copper supply networks of Bronze Age Europe has remained poorly understood so far. The region’s intermediary position between copper production centres in northeastern Italy and the inland Balkans, which from at least the beginning of the Late Bronze Age (14th century BC) were largely supplied with Italian copper is of particular relevance. The results presented here contribute to a more comprehensive understanding of regional metallurgical practices and help refine our reconstruction of the chronological and spatial dynamics of copper distribution across Central Europe, Italy, and the Balkans.

Assessing monthly habitat quality for bumblebees in grasslands using a habitat trait model: a case study in Worcestershire, UK - Andrea Tapia-Arenas; Richard F. Comont; Fleur Visser; Kate Ashbrook (Journal of Insect Conservation, 2026)
Bumblebee decline in the UK has been associated with land use change from diverse meadows to intensive agriculture. While grasslands can offer the resources that bumblebees need to survive and thrive, the precise availability of resources through the year and between sites can vary due to differences in species composition and management. In this study, we surveyed bumblebee abundance using transects and monitored their habitat using 1-square-meter plots in 2021 and 2022 across five semi-natural grasslands located in Worcestershire, UK. These data were used to build a monthly bumblebee abundance prediction with a Generalized Linear Effects Model (GLME), which was used to rank the sites based on the predicted number of bumblebees. The selected model indicated that bumblebee abundance was most strongly associated with the proportion of the preferred bumblebee forage species and floral richness. Vegetation height and the variation of floral resources coverage had small, non-significant coefficients in this dataset, but were retained as ecologically relevant descriptors and for their contribution to cross-validated performance. Our model successfully identified sites with the lowest bumblebee abundance, and the monthly assessments provided information to guide management actions to improve the habitat quality at a site scale. Our findings are foundational, suggesting directions for future research in broader geographical contexts to validate and refine habitat assessment methods. Implications for insect conservation This study highlights crucial implications for insect conservation, demonstrating that targeted management actions based on monthly habitat assessments can significantly enhance the quality of grassland habitats. This approach not only supports bumblebee populations but also other pollinator species within agricultural landscapes.

A case for monitoring fungi of clinical relevance at beaches: enterococci measures do not correlate with all disease risks - Larissa Montás-Bravo; Helena M. Solo-Gabriele; Débora F. Gil; Ayaaz Amirali; Sebastian P. Arenas; Sofia Hoffman; Adriana Jimenez; Alexandre Mendonça; Rivka Reiner; Raquel Sabino; Konstantina Sarioglou; Mark E. Sharkey; et al. (Environmental Monitoring and Assessment, 2026)
Fungal disease is on the rise, coupled with fungal pathogens increasing in geographic range. Studies have shown that viable fungal pathogens may be present in beach sand and water, and consequently, efforts are ongoing in Europe to develop guidelines for fungi levels at beaches. In the USA, fungal diseases are a growing concern, and yet, they are not subject to public health reporting, and beach environments are currently not routinely monitored for fungal pathogens. This study measured fungal and enterococci levels at two beaches within a subtropical environment in Miami, FL. Samples were analyzed by culture-based methods, with fungi species confirmation by targeted PCR and sequencing. A unique aspect of this study is the analysis with higher incubation temperatures (37 °C and 40 °C) to isolate mesophilic fungi that can cause invasive infections. Results show that levels of fungi were strongly influenced by sample matrix (sand or water). The most common fungal species observed belonged to the Aspergillus and Candida genera, with the isolation of 25 taxa with reports of causing infections, of which 20 were previously reported to exhibit resistance to some or all classes of antifungals available. Results emphasize the need for fungal specific analyses to better understand beach-related disease risks. Given the current increase in cases of fungal diseases and the presence of viable fungi in the environment, integrating fungal measurements in routine microbiological monitoring programs is critical for assessing the beach transmission of pathogenic fungal disease and the control of emerging fungal pathogens.

Response of intertidal fucales to low-tide heat stress at their southern distributional limit - Luís F. Pereira; Cátia Monteiro; João Seródio; João Silva; Rui Seabra; Fernando P. Lima; Jorge Teixeira; Francisco Arenas (Marine Environmental Research, 2025)

P27-19 CLP criteria and ECHA guidance for classification of endocrine disruptors - K. Myöhänen; N. Andersson; M. Sobanska; F. Pellizzato; M. Arena (Toxicology Letters, 2025)

Evaluating the capability of tannic acid-modified biochar in sequestering metal ions and in enhancing soil health - L. Santorufo; G. Maglione; G. Costanzo; G. De Tommaso; F. De Paola; G. Roviello; E. Chianese; C. Ferone; F. Polimeno; M. Riccardi; G. Maisto; M. Iuliano; et al. (International Journal of Environmental Science and Technology, 2025)
Pollution of soils is one of the currently significant environmental concerns. Heavy metals that contaminate the soil can have harmful effects on crops, enter the food chain, and pose a threat to human health. Various approaches have been employed in the past to remediate heavy metal-contaminated soils for agricultural use, including the use of biochar and its modified forms through physical or chemical methods. In the present study, the suitability of tannic acid as a biochar modifier was evaluated for the first time with the aim of enhancing its ability to adsorb Cd and Pb, thereby reducing their transfer from soil to plants. A mesocosm trial was set-up using three treatments: control, unmodified biochar, and tannic acid-modified biochar and their impact was evaluated on soil characteristics and plant physiology. The FT-IR spectra demonstrate that tannic acid-modified biochar considerably improved its capability to absorb Cd but worsened those for Pb and this occurred due to an increase in oxygen-containing functional groups and a reduction in total pore volume, respectively. Tannic acid-modified biochar application increased the carbon and nitrogen concentrations in the soil, as well as the microbial biomass and activities. Lettuce plants grown on soil amended with modified biochar accumulated a low Cd amount in roots but a high Pb amount in leaves that reduced the photosynthetic pigments and the photosynthetic rates and increased the antioxidant response. It is found that tannic acid treatment of biochar is effective for the remediation of Cd-contaminated soils but not for those polluted by Pb.

Full-Resolution Sentinel-3 Satellite Observations of Phytoplankton Phenology in Optically Complex Waters of the Northern Patagonian Shelf - Maximiliano Arena; Paula Pratolongo; Hubert Loisel; Manh Duy Tran; Daniel S. F. Jorge; Ana Laura Delgado (Estuaries and Coasts, 2025)
In this study, we characterized phytoplankton biomass variability in El Rincón, a shallow and biologically productive coastal region in the Patagonian Continental Shelf. We used as a proxy 7 years (2017–2024) of high-resolution Sentinel-3 OLCI satellite data to capture the fine scale spatio-temporal variability of Chl- a in this region. To obtain Chl- a concentration, we applied a regionally validated algorithm (MuRB&NDCI) which provides more accurate Chl- a estimates compared to traditional algorithms, particularly in optically complex waters. Self-organizing maps (SOM) neural network was applied to identify four distinct bio-geographical regions with unique bloom dynamics. The phenological estimates revealed that phytoplankton blooms typically initiate in fall (March), peak during winter (May–August), and are more pronounced near the Bahía Blanca Estuary (BBE), where nutrient and sediment inputs drive high productivity. The findings presented in this work highlight the utility of Optical Water Class–based algorithms for capturing the fine-scale spatiotemporal variability of Chl- a in coastal systems. This study advances our understanding of phytoplankton dynamics in El Rincón and underscores the importance of customized satellite-derived approaches for monitoring and managing productivity in shallow coastal environments.

Global drifters: The ecological role of non-native macroalgae as beach wrack subsidies - Iván F. Rodil; Filipa Bessa; Alexandra Baeta; Francisco Arenas (Estuarine, Coastal and Shelf Science, 2025)

Enantioselective toxicity of propranolol on marine diatoms: Assessing growth, energy metabolism and oxidative damage in Phaeodactylum tricornutum - Marina Arenas; Eduardo Feijão; Irina A. Duarte; Vanessa F. Fonseca; Irene Aparicio; Esteban Alonso; Bernardo Duarte (Marine Pollution Bulletin, 2025)

Petrogenesis of ultramafic rocks from the Neoproterozoic Bou Azzer Ophiolite (Morocco): new insights into a long-standing geodynamic question - N. Pujol-Solà; J.A. Proenza; A. Cambeses; F. Haissen; H. Escalona-Orellana; D. Domínguez-Carretero; I. Novo-Fernández; R. Arenas; L. Maacha; M. Ikenne; A. Garcia-Casco (International Geology Review, 2025)

Hydrogeology and Groundwater Flow in a Hummocky Prairie Pothole Complex, Northern Iowa - Keith E. Schilling; Matthew T. Streeter; Phil Kerr; Calvin F. Wolter; Elliot Anderson; Alejandro Gomez; Antonio Arenas-Amado (Wetlands, 2025)

Assessment of pillar-array electrodes for electrochemical flow reactors using a novel hydrodynamic electrode performance factor - Michiel De Rop; Luis F. Arenas; Renée De Wolf; Jonas Hereijgers (Chemical Engineering Journal, 2024)

European Network for Optimization of Veterinary Antimicrobial Therapy (ENOVAT) guidelines for antimicrobial use in canine acute diarrhoea - L.R. Jessen; M. Werner; D. Singleton; C. Prior; F. Foroutan; A.A. Ferran; C. Arenas; C. R. Bjørnvad; E. Lavy; F. Allerton; K. Allensbach; L. Guardabassi; et al. (The Veterinary Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Quartz OSL dating of ancient ceramics fragments from the Churajon archaeological complex in Arequipa, Peru - Carlos D. Gonzales-Lorenzo; Yolanda Pacompia; Nilo F. Cano; René R. Rocca; Jose F.D. Chubaci; Henry S.L. Sullasi; Zaida V. Vilca; Oscar Ayca-Gallegos; Jorge Ayala-Arenas (Quaternary International, 2024)

P20-10 Embracing regulatory compliance: Genetox meets generation SEND - S. Salazar Arenas; C. Bapat; M. Ellison; M. Wasko; F. Hall (Toxicology Letters, 2024)

Perezone and its phenyl glycine derivative induce cytotoxicity via caspases on human glial cancer cells - M. Mirian Estévez-Carmona; M. Teresa Ramírez-Apan; Montserrat Zaragoza-Ojeda; Anita Vega-Miranda; Francisco Arenas-Huertero; William F. Reynolds; Marco A. Obregón-Mendoza (Natural Product Research, 2024)

A novel membrane-based process to concentrate nutrients from sidestreams of an Urban Wastewater Treatment Plant through captured carbon dioxide from biogas - Judith González-Arias; Francisco M. Baena-Moreno; Mónica Rodríguez-Galán; Benito Navarrete; Luis F. Vilches-Arenas (Science of The Total Environment, 2024)

Artificial Light at Night Reduces Flashing in Photinus and Photuris Fireflies During Courtship and Predation - Juan S. Hillón-Salas; Juan D. Pineda-Dueñas; Ana M. Romero-Chacón; Juliana Fonseca-Tellez; Manuela Cardona-Restrepo; Sofía C. Garrido-Villegas; Diego Mejía-Tovar; Camilo Arenas-Ríos; Laia Gaitán-Botero; Zulma S. Barón-Garzón; Andrés F. Robayo-Salek; Harold Pulido-Guarín; et al. (Journal of Insect Behavior, 2024)
Artificial light at night (ALAN) affects species-specific communication in a wide range of nocturnal species, including fireflies (Lampyridae). Fireflies rely on bioluminescent signals for communicating. In this study, we conducted two manipulative field experiments to evaluate the effect of artificial light at night on the flashing activity of male and female neotropical fireflies during courtship and predation. Our results showed a significant reduction in the flashing activity of both males and females exposed to ALAN during courtship and predation. Remarkably, the effect of ALAN on male flashing activity seems to be independent of female flashing activity. In conclusion, ALAN disrupts bioluminescent intraspecific (courtship) and interspecific (predation) communication, which in turn could influence mating success, thus negatively affecting neotropical firefly populations in the long term. Our findings contribute to understanding the challenges faced by neotropical firefly communities in the presence of ALAN.

Plant metabolic response to stress in an arid ecosystem is mediated by the presence of neighbors - Alicia Montesinos‐Navarro; Maria F. López‐Climent; Rosa M. Pérez‐Clemente; Cristina Arenas‐Sánchez; Ricardo Sánchez‐Martín; Aurelio Gómez‐Cadenas; Miguel Verdú (Ecology, 2024)
Plant neighbors in arid environments can ameliorate abiotic stress by reducing insolation, but they also attract herbivores and pathogens, especially when neighbors are close relatives that share similar antagonists. Plants' metabolic profiles provide a chemical fingerprint of the physiological processes behind plant responses to different environmental stresses. For example, abscisic acid and proline, mainly involved in stomatal closure and osmotic adjustment, can induce plant responses to abiotic stress, while jasmonic acid and salicylic acid primarily regulate plant defense to herbivory or pathogens. Neighbor plants can generate contrasting ecological contexts, modulating plant responses to abiotic and biotic stresses. We hypothesize that plant metabolic profile is modulated by its neighbors in a vegetation patch, expecting a higher investment in metabolites related to biotic‐stress tolerance (i.e., herbivory or pathogens) when growing associated with other plants, especially to phylogenetically close relatives, compared to plants growing alone. We show that plants from five species growing with neighbors invest more in biotic‐stress tolerance while their conspecifics, growing alone, invest more in abiotic‐stress tolerance. This tendency in plants' metabolic profiles was not affected by the phylogenetic diversity of their neighborhood. Linking physiological snapshots with community processes can contribute to elucidating metabolic profiles derived from plant–plant interactions.

Efficacy of antimicrobial and nutraceutical treatment for canine acute diarrhoea: A systematic review and meta-analysis for European Network for Optimization of Antimicrobial Therapy (ENOVAT) guidelines - K. Scahill; L.R. Jessen; C. Prior; D. Singleton; F. Foroutan; A.A. Ferran; C. Arenas; C.R. Bjørnvad; E. Lavy; F. Allerton; J.S. Weese; K. Allenspach; et al. (The Veterinary Journal, 2024)

Geochemistry and mineralogy of muds and thermal waters from mud volcanoes in the NW Caribbean Coast of Colombia and their potential for pelotherapy - Maurizio Palmisano; Giuseppina Balassone; Sabino Maggi; Alexander Armesto Arenas; Iber M. Banda Guerra; Luis E. Correa Valero; Feliciano Ippolito; Nicola Mondillo; David F. Morales Giraldo; Angela Mormone; Annamaria Pellino; Francesco Putzolu; et al. (CATENA, 2024)

Removal of organic compounds in wastewater using cocoa shell‑based activated carbon–SiO2 nanoparticles - Adan Y. León; José D. Contreras-Arenas; Cristian F. Garnica-Fuentes; Michell A. Jiménez-Caballero; Diego F. Pinto-Hernández; Emiliano Ariza-León; Darío Y. Peña-Ballesteros; Daniel R. Molina-Velasco (Environment, Development and Sustainability, 2023)
This work aimed to use low-cost residual cocoa shell biomass for the preparation of activated carbon with different amounts of SiO 2 nanoparticles using the coprecipitation method. The use of residual plant biomass seeks to strengthen the challenges of the bioeconomy in the generation of value-added products for the agro-industry. Subsequently, the adsorption capacity of phenol and 3,4-dimethoxybenzyl alcohol as representative species of persistent organic pollutants was quantified. The chemical activation of the carbon was carried out at 480 °C during 30 min with a 1.5 phosphoric acid (H 3 PO 4 ) impregnation ratio. The activated carbons were characterized by Fourier transform infrared spectroscopy (FTIR), showing the presence of functional groups associated with substances such as phenols, carboxylic acids, aromatic rings, and SiO 2 . Also, activated carbons were structurally characterized with scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS), finding that the granules had structured surfaces but with irregular size and disordered channels, which facilitates the impregnation of SiO 2 nanoparticles onto the activated carbon surface. The adsorption study of the organic compounds was carried out using UV–Vis spectroscopy. The adsorption isotherms, which were adjusted to the Langmuir, Freundlich and Temkin models, were determined with correlation coefficients of 0.9835, 0.9885 and 0.987. On the other hand, the adsorbent materials achieved removal percentages around 97.9% and 97.8% for phenol and 3,4-dimethoxybenzyl alcohol, respectively. The results showed that activated carbons with SiO2 nanoparticles increased the specific surface area by up to 20%. Therefore, this property allows a greater interaction of contaminants at the time of adsorption. Graphical abstract

Genetic variants of antioxidant and xenobiotic metabolizing enzymes and their association with prostate cancer: A meta-analysis and functional in silico analysis - Beatriz Álvarez-González; Patricia Porras-Quesada; Verónica Arenas-Rodríguez; Alba Tamayo-Gómez; Fernando Vázquez-Alonso; Luis Javier Martínez-González; Antonio F. Hernández; María Jesús Álvarez-Cubero (Science of The Total Environment, 2023)

Unbalancing Zur (FurB)‐mediated homeostasis in Anabaena sp. PCC7120: Consequences on metal trafficking, heterocyst development and biofilm formation - Irene Olivan‐Muro; Cristina Sarasa‐Buisan; Jorge Guio; Jesús Arenas; Emma Sevilla; Maria F. Fillat (Environmental Microbiology, 2023)
Zinc is required for the activity of many enzymes and plays an essential role in gene regulation and redox homeostasis. In Anabaena ( Nostoc ) sp. PCC7120, the genes involved in zinc uptake and transport are controlled by the metalloregulator Zur (FurB). Comparative transcriptomics of a zur mutant (Δ zur ) with the parent strain unveiled unexpected links between zinc homeostasis and other metabolic pathways. A notable increase in the transcription of numerous desiccation tolerance‐related genes, including genes involved in the synthesis of trehalose and the transference of saccharide moieties, among many others, was detected. Biofilm formation analysis under static conditions revealed a reduced capacity of Δ zur filaments to form biofilms compared to the parent strain, and such capacity was enhanced when Zur was overexpressed. Furthermore, microscopy analysis revealed that zur expression is required for the correct formation of the envelope polysaccharide layer in the heterocyst, as Δ zur cells showed reduced staining with alcian blue compared to Anabaena sp. PCC7120. We suggest that Zur is an important regulator of the enzymes involved in the synthesis and transport of the envelope polysaccharide layer, influencing heterocyst development and biofilm formation, both relevant processes for cell division and interaction with substrates in its ecological niche.

Combined effects of climate change and environmentally relevant mixtures of endocrine disrupting compounds on the fitness and gonads' maturation dynamics of Nucella lapillus (Gastropoda) - H. Morais; F. Arenas; C. Cruzeiro; S. Galante-Oliveira; P.G. Cardoso (Marine Pollution Bulletin, 2023)

Potential for water and metal recovery from acid mine drainage by combining hybrid membrane processes with selective metal precipitation - Elena León-Venegas; Luis F. Vilches-Arenas; Custodia Fernández-Baco; Fátima Arroyo-Torralvo (Resources, Conservation and Recycling, 2023)

VIGIRISKS platform, a web-tool for single and multi-hazard risk assessment - C. Negulescu; F. Smai; R. Quique; A. Hohmann; U. Clain; R. Guidez; A. Tellez-Arenas; A. Quentin; G. Grandjean (Natural Hazards, 2023)
Enabling storing, scenario design, documentation, access and execution of scientific computations for multirisks mapping is the aim of the VIGIRISKS web platform currently designed and developed by the BRGM (French Geological Survey). VIGIRISKS platform insures geohazards data management, reproducibility of risks calculations, allows information transparency and improving efficiency by easing collaborative work and sharing results and practices. The scientific scope is multirisk mapping, including cascading effects, in the domain of natural hazard (earthquake, landslide and submersion) from the phenomenon modelling to the impact evaluation on exposed elements such as buildings. VIGIRISKS web platform initially designed for BRGM experts aims to be in a long-term an open repository for national and international experts working on natural hazards management. Integration and deployment of new datasets and computational processes oriented towards risks mapping is as automatic as possible for the convenience of users.

Sound absorbing porous concretes composed of different solid wastes - Celia Arenas; José D. Ríos; Héctor Cifuentes; Luis F. Vilches; Carlos Leiva (European Journal of Environmental and Civil Engineering, 2022)

Setting Performance Indicators for Coastal Marine Protected Areas: An Expert-Based Methodology - Mariana Cardoso-Andrade; Henrique Queiroga; Mafalda Rangel; Inês Sousa; Adela Belackova; Luís Bentes; Frederico Oliveira; Pedro Monteiro; Nuno Sales Henriques; Carlos M. L. Afonso; Ana F. Silva; Bernardo R. Quintella; et al. (Frontiers in Marine Science, 2022)
Marine Protected Areas (MPAs) require effective indicators to assess their performance, in compliance with the goals of relevant national and international commitments. Achieving and prioritizing shortlists of multidisciplinary indicators demands a significant effort from specialists to depict the multiple conservation and socioeconomic interests, and the large complexity of natural systems. The present paper describes a structured expert-based methodology (process and outputs) to co-define a list of multidisciplinary MPA performance indicators. This work was promoted by the management authority of coastal MPAs in mainland Portugal to gather a consensual and feasible list of indicators that would guide the design of a future national monitoring program. Hence, Portuguese coastal MPAs served as a case study to develop such a process between 2019 and 2020. In the end, participants (1) agreed on a shortlist of prioritized indicators ( i.e. , environmental, governance, and socioeconomic indicators) and (2) defined minimum monitoring frequencies for the indicators in this list, compatible with the potential replicability of the associated survey methods. The present approach recommends that management plans incorporate monitoring procedures and survey methods, with a validated list of indicators and associated monitoring periodicity, agreed among researchers, MPA managers and governance experts. The proposed methodology, and the lessons learned from it, can support future processes aiming to define and prioritize MPA performance indicators.

Modeling the sulfamethoxazole degradation by active chlorine in a flow electrochemical reactor - Ricardo E. Palma-Goyes; Fabiola S. Sosa-Rodríguez; Fernando F. Rivera; Jorge Vazquez-Arenas (Environmental Science and Pollution Research, 2022)

Synthesis of polyamino styrene from post-consumption expanded polystyrene and analysis of its CO2 scavenger capacity - D. R. Merchán-Arenas; A. F. Murcia-Patiño (International Journal of Environmental Science and Technology, 2021)

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Embedding existential psychology within psychedelic science: reduced death anxiety as a mediator of the therapeutic effects of psychedelics - Sam G. Moreton; Luke Szalla; Rachel E. Menzies; Andrew F. Arena (Psychopharmacology, 2020)

Assessing durability properties of noise barriers made of concrete incorporating bottom ash as aggregates - Carlos Leiva; Celia Arenas; Luis F. Vilches; Fatima Arroyo; Yolanda Luna-Galiano (European Journal of Environmental and Civil Engineering, 2019)

Persistent increase of I.V. cocaine self-administration in a subgroup of C57BL/6J male mice after social defeat stress - Danielle T. Arena; Herbert E. Covington; Joseph F. DeBold; Klaus A. Miczek (Psychopharmacology, 2019)

Variability of regional atmospheric moisture over Northern South America: patterns and underlying phenomena - I. Hoyos; J. Cañón-Barriga; T. Arenas-Suárez; F. Dominguez; B. A. Rodríguez (Climate Dynamics, 2019)

Agricultural conservation practices in Iowa watersheds: comparing actual implementation with practice potential - Trevor J. Rundhaug; Greg R. Geimer; Chad W. Drake; Antonio Arenas Amado; A. Allen Bradley; Calvin F. Wolter; Larry J. Weber (Environmental Monitoring and Assessment, 2018)

On time-domain uncoupled analyses for offshore wind turbines under seismic loads - F. Santangelo; G. Failla; F. Arena; C. Ruzzo (Bulletin of Earthquake Engineering, 2018)

Genetic and morphological analysis of Berberis microphylla G. Forst. accessions in southern Tierra del Fuego - E. Giordani; M. Müller; F. Gambineri; D. Paffetti; M. Arena; S. Radice (Plant Biosystems, 2017)

Topiramate increases the rewarding properties of cocaine in young-adult mice limiting its clinical usefulness - M. C. Arenas; A. Mateos-García; C. Manzanedo; M. Rodríguez-Arias; M. A. Aguilar; F. Navarrete; M. S. García Gutiérrez; J. Manzanares; J. Miñarro (Psychopharmacology, 2016)

Arsenopyrite weathering under conditions of simulated calcareous soil - René H. Lara; Leticia J. Velázquez; Jorge Vazquez-Arenas; Martine Mallet; Manuel Dossot; Israel Labastida; Fabiola S. Sosa-Rodríguez; León F. Espinosa-Cristóbal; Miguel A. Escobedo-Bretado; Roel Cruz (Environmental Science and Pollution Research, 2016)

Ediacaran to Cambrian oceanic rocks of the Gondwana margin and their tectonic interpretation - Jürgen F. von Raumer; Gérard M. Stampfli; Ricardo Arenas; Sonia Sánchez Martínez (International Journal of Earth Sciences, 2015)

Alteration of Macroalgal Subsidies by Climate-Associated Stressors Affects Behavior of Wrack-Reliant Beach Consumers - Iván F. Rodil; Paloma Lucena-Moya; Celia Olabarria; Francisco Arenas (Ecosystems, 2015)

The regime of climate-related disturbance and nutrient enrichment modulate macroalgal invasions in rockpools - Iacopo Bertocci; J. Domínguez Godino; C. Freitas; M. Incera; R. Araújo; A. Bio; F. Arenas; I. Sousa-Pinto; P. A. Reis; R. Domínguez (Biological Invasions, 2015)

B25716/1: a novel albumin-binding Gd-AAZTA MRI contrast agent with improved properties in tumor imaging - E. Gianolio; C. Cabella; S. Colombo Serra; G. Valbusa; F. Arena; A. Maiocchi; L. Miragoli; F. Tedoldi; F. Uggeri; M. Visigalli; P. Bardini; S. Aime (JBIC Journal of Biological Inorganic Chemistry, 2014)

Functional diversity and climate change: effects on the invasibility of macroalgal assemblages - F. Vaz-Pinto; C. Olabarria; I. Gestoso; E. Cacabelos; M. Incera; F. Arenas (Biological Invasions, 2013)

The birds and the seeds: opportunistic avian nectarivores enhance reproduction in an endemic montane aloe - Gina Arena; Craig T. Symes; E. T. F. Witkowski (Plant Ecology, 2013)

Physical factors driving intertidal macroalgae distribution: physiological stress of a dominant fucoid at its southern limit - Brezo Martínez; F. Arenas; M. Rubal; S. Burgués; R. Esteban; I. García-Plazaola; F. L. Figueroa; R. Pereira; L. Saldaña; I. Sousa-Pinto; A. Trilla; R. M. Viejo (Oecologia, 2012)

Risk assessment of the lead intake by consumption of red deer and wild boar meat in Southern Spain - J.S. Sevillano Morales; R. Moreno Rojas; F. Pérez-Rodríguez; A. Arenas Casas; M.A. Amaro López (Food Additives & Contaminants: Part A, 2011)

Gas exchange and leaf metabolism of irrigated maize at different growth stages - L. Vitale; C. Arena; P. Carillo; P. Di Tommasi; B. Mesolella; F. Nacca; A. Virzo De Santo; A. Fuggi; V. Magliulo (Plant Biosystems, 2011)

Excessive skeletal muscle recruitment during strenuous exercise in McArdle patients - Dale E. Rae; Timothy D. Noakes; Alejandro F. San Juan; Margarita Pérez; Gisela Nogales-Gadea; Jonatan R. Ruiz; María Morán; Miguel A. Martín; Antoni L. Andreu; Joaquín Arenas; Alejandro Lucia (European Journal of Applied Physiology, 2010)

The effect of an anti-inflammatory pentapeptide produced by Entamoeba histolytica on gene expression in the U-937 monocytic cell line - R. Silva-García; I. Estrada-García; R. Ramos-Payán; A. Torres-Salazar; M. E. Morales-Martínez; D. Arenas-Aranda; J. A. Giménez-Scherer; F. Blanco-Favela; M. G. Rico-Rosillo (Inflammation Research, 2008)

Nestin, a neuroectodermal stem cell marker molecule, is expressed in Leydig cells of the human testis and in some specific cell types from human testicular tumours - Maria V. T. Lobo; Maria I. Arenas; F. Javier M. Alonso; Gonzalo Gomez; Eulalia Bazn; Carlos L. Pano; Eldiberto Fernndez; Benito Fraile; Ricardo Paniagua; Alfredo Moyano; Enrique Caso (Cell and Tissue Research, 2004)

An Imported Case of Blastomyces Dermatitidis Infection in Mexico - Roberto Velázquez; B. Muñoz-Hernández; R. Arenas; M. L. Taylor; F. Hernández-Hernández; M. E. Manjarrez; R. López-Martínez (Mycopathologia, 2003)

Removal of H2S by Metal Ferrites Produced in the Purification of Metal-Bearing Waste Water. Study of the Reaction Mechanism - E. Barrado; F. Prieto; B. Lozano; F. J. Arenas; J. Medina (Water, Air, & Soil Pollution, 2001)

Structural and kinematic analysis of the Corredoiras detachment: evidence for early Variscan synconvergent extension in the Ordenes Complex, NW Spain - F. Díaz García; J. R. Martínez Catalán; R. Arenas; P. González Cuadra (International Journal of Earth Sciences, 1999)

Lectin histochemistry study in the human vas deferens - María I Arenas; Juan F. Madrid; Fermín R. Bethencourt; B. Fraile; R. Paniagua (Glycoconjugate Journal, 1998)